Exploring Criteria and Critical Factors for Governmental Projects Implementation in Yemen: A Case Study - Al-Sabahi, Mohammed H.; Al-Hamidi, Amal A.; Ramly, Ahmed; Mat Rejab, Kamarudzaman (Journal of Surveying, Construction and Property, 2014)
Success is the ultimate goal to be achieved in any project; consequently, studies concerning project success are essential. The purpose of this study is to evaluate significant success criteria and identify critical success factors to ensure project success. Furthermore, this research aids in changing the method of project implementation in Yemen to help conserve time, money, and natural resources. To explore the process and project implementation in Yemen; to evaluate the criteria for time, cost, and quality determination; and to identify the success and failure factors of project, are the three goals of this study. Case study method and structured questionnaire survey method are applied in this research. Fieldwork involves the investigation of the stages of a project in Yemen: from the design stage, the tender stage, and to the construction stage. Thematic narrative analysis is conducted to analyze the case studies. Data are examined with the statistical package for social sciences (SPSS). Three success criteria have been recognized, twenty success factors have been ranked and documented, while thirty-one failure factors have been identified. Fieldwork in Yemen revealed that professionals involved in project implementation can develop the construction industry if subjected to strict regulations.